Early-stage sustainability assessment of enzyme production in the framework of lignocellulosic biorefinery. (20th February 2021) - Bello, Sara; Pérez, Noelia; Kiebist, Jan; Scheibner, Katrin; Sánchez Ruiz, María Isabel; Serrano, Ana; Martínez, Ángel T.; Feijoo, Gumersindo; Moreira, Maria Teresa
Abstract: The use and integration of enzymatic processes for the biotransformation of biomass within the biorefinery framework creates the need to confirm whether these novel production systems are in the route to environmental sustainability. In this study, the environmental profiles of the production of two oxidative enzymes, hydroxymethylfurfural oxidase (HMFO) from Methylovorus and unspecific peroxygenase (UPO) from Chaetomium globosum ( Cg lUPO) for the enzymatic production of FDCA as precursor of bioplastics were analyzed. Laboratory-scale experiments allowed the identification of the consumption of energy, with over 80% share in every impact category for HMFO and chemicals and energy in Cgl UPO as primary hotspots of the systems. The results are transposed for HMFO when laboratory inventories were extrapolated to full scale processing, showing that impacts are attributed not only to energy demand but also to the use of chemicals required for the formulation of the culture medium. In terms of process units, the fermenter, where enzyme production takes place, corresponds to the stage that contributes the most to the environmental impacts, with a 57% share, followed by the downstream separation scheme (37%). Extrapolation of laboratory data to full-scale also represented a change in the relative difference of the impact per functional unit of 45% for CgI UPO. The endpoint damage categories showed a significant reduction in their full-scale impacts to about half the burden. The analysis of the outcomes of the uncertainty analysis showed that the resource depletion category had the least dispersion of data, while the level of uncertainty is more relevant for human health, as it takes into account the combined effect of a larger number of impact categories and the processes involved. This study shows that, although being bio-based catalysts, the production of enzymes involves several steps which may incur in environmental impact. Thus, it is recommended that enzymes are carefully included within the system boundaries for their evaluation, since they could be the major hotspot in the biorefinery value chain. De-fossilization of the plastic industry will be possible with thoroughly optimized bio-transformations, with carbon-based media from residual resources, minimized use of chemicals and the implementation of energy integration measures. Highlights: Two oxidative enzymes were evaluated through midpoint and endpoint LCA. Laboratory scale data is not representative for LCA evaluation. The appropriate upscaling techniques should be followed for LCA at large scale. Electricity is a clear hotspot in HMFO laboratory production. Operations in the fermenting stage represent the gross of environmental impacts.